2020
DOI: 10.7759/cureus.11613
|View full text |Cite
|
Sign up to set email alerts
|

Similarities Between Depression and Neurodegenerative Diseases: Pathophysiology, Challenges in Diagnosis and Treatment Options

Abstract: Depressive disorder and neurodegenerative diseases are two different clinical entities. Depression is a common psychiatric disorder in the general population. However, when present concomitantly with neurodegenerative disorders, its diagnosis becomes challenging. In many cases, patients remain undiagnosed and hence, untreated, worsening the prognosis of the neurodegenerative diseases and impairing the quality of life. One of the possible reasons for the difficulties in diagnosis in such cases is that both cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Recurrent major depression was a risk factor for Alzheimer’s disease, also Alzheimer’s disease constituted a risk factor for depression ( Aznar and Knudsen, 2011 ). Reports have revealed that similar changes in the neuroplasticity, morphology, and neurotransmission in the brain seemed to be associated to depression and cognitive dysfunction ( Hussain et al, 2020 ). Alzheimer’s disease intrinsically deteriorates affective regulation, a critical capacity in the resistance to depression in the face of life stresses ( Nash et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recurrent major depression was a risk factor for Alzheimer’s disease, also Alzheimer’s disease constituted a risk factor for depression ( Aznar and Knudsen, 2011 ). Reports have revealed that similar changes in the neuroplasticity, morphology, and neurotransmission in the brain seemed to be associated to depression and cognitive dysfunction ( Hussain et al, 2020 ). Alzheimer’s disease intrinsically deteriorates affective regulation, a critical capacity in the resistance to depression in the face of life stresses ( Nash et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional and anatomical differences between the hemispheres have also been demonstrated [ 16 - 17 ]. Many clinical parameters have been evaluated in prognosis studies on patients with PD [ 18 - 20 ]. However, to the best of our knowledge, the impact of the asymmetrical presentation of clinical symptoms on the prognosis of patients with PD has not previously been evaluated, although many researchers believe that motor predominance is essential for a diagnosis of parkinsonism.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms are reported in AD prior to mild cognitive impairment (MCI) with a prevalence of about 20% [ 28 , 31 ], as well as in preclinical bvFTD, where a prevalence up to 40% has been described [ 23 , 32 ]. Depression during the preclinical stages of AD and bvFTD can be often associated with other affective symptoms and mood changes [ 15 , 33 ]. Similarly, affective symptoms are already present at the time of diagnosis in PD and HD in a percentage of cases up to 30%, and may precede neurological symptoms of several years [ 5 , 34 , 35 ].…”
Section: Psychiatric Symptoms In the Clinical Course Of Neurodegenerative And Neuroinflammatory Diseasesmentioning
confidence: 99%
“…Noteworthy, depressive and anxiety symptoms are listed among clinical markers of prodromal PD in the most updated diagnostic criteria [ 36 , 37 ]. The lack of an accurate evaluation of psychiatric symptoms, i.e., insufficient attention dedicated to their late-life onset and to a negative personal psychiatric history, often leads to the diagnosis of a primary psychiatric disorder in these subjects [ 15 , 38 ]. As a consequence, inappropriate psychopharmacological treatment is frequently prescribed, further affecting the clinical presentation, and contributing at the same time to the lack of adequate medical care for the underlying neurological condition [ 33 , 39 ].…”
Section: Psychiatric Symptoms In the Clinical Course Of Neurodegenerative And Neuroinflammatory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation